PENDIDIKAN NARKOTIKA UNTUK MEWUJUDKAN GENERASI PENERUS BANGSA YANG BAIK DI INDONESIA - Rianda Prima Putri (Ensiklopedia Education Review, 2019)
Narcotics has a broader scope both in terms of norms, material scope and aggravated criminal threats. The broader coverage is not only based on the above factors, but also because of the development of needs and the fact that the values and norms in the applicable regulations are no longer effective as means to prevent and eradicate the abuse and illicit trafficking of narcotics. One of the new material in Law Number 35 of 2009 concerning Narcotics, is divided into 3 (three) groups, regarding how the intended classification of each group has been formulated in Article 6 paragraph (1) of the Narcotics Law. Narcotics education is very important to do in Indonesia, in order to create the next generation of the nation.